2015
DOI: 10.1186/s12913-015-0923-z
|View full text |Cite
|
Sign up to set email alerts
|

The readiness of the national health laboratory system in supporting care and treatment of HIV/AIDS in Tanzania

Abstract: BackgroundStrong health laboratory systems and networks capable of providing high quality services are critical components of the health system and play a key role in routine diagnosis, care, treatment and disease surveillance. This study aimed to assess the readiness of the national health laboratory system (NHLS) and its capacity to support care and treatment of HIV/AIDS in Tanzania.MethodsA documentary review was performed to assess the structure of the health system with reference to the status and capacit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 15 publications
(22 reference statements)
1
8
0
Order By: Relevance
“…The test and treat strategy, the recommended and increasing donor support for routine HVL testing, and the consequent decrease in CD4 count testing as per guidelines all likely contributed to the lower access to CD4 count testing observed in our study [43][44][45]. A declining trend of CD4 count measurement has been observed in many southern African countries since the beginning of the Test and Treat era in alignment with our findings [46][47][48]. Despite this, the considerably high access to HVL testing observed in Shinyanga likely reflects the donor-funded status of this service.…”
Section: Discussionsupporting
confidence: 81%
“…The test and treat strategy, the recommended and increasing donor support for routine HVL testing, and the consequent decrease in CD4 count testing as per guidelines all likely contributed to the lower access to CD4 count testing observed in our study [43][44][45]. A declining trend of CD4 count measurement has been observed in many southern African countries since the beginning of the Test and Treat era in alignment with our findings [46][47][48]. Despite this, the considerably high access to HVL testing observed in Shinyanga likely reflects the donor-funded status of this service.…”
Section: Discussionsupporting
confidence: 81%
“…This is contrary to the national guidelines which stipulate that all hospitals and health centres should provide HIV diagnostic services for detection of infection status and supportive tests for management and care of PLHA [18, 30]. Furthermore, the low coverage of HIV care and treatment services at low level HFs and in rural areas, which serve the majority of the population [31], suggests that most of the PLHA may have limited access to the critically needed services. However, with laboratories in 13.4% of the dispensaries and most of the health centres (95.2%) in rural areas, there exists a room for scaling up of HIV diagnostic and supportive services in the country.…”
Section: Discussionmentioning
confidence: 95%
“…(Hickman et al, 2014). A paper by Mboera et al (2015) found that a wellestablished National Health Laboratory System was in place in Tanzania, however, the coordination of HIV laboratory services was found to be weak. Physical access to health services has significantly improved in Tanzania with the construction and renovation of PHC facilities in rural areas.…”
Section: Service Deliverymentioning
confidence: 99%
“…Strong health laboratory systems and networks capable of providing high quality services are critical components of the health system and play a key role in routine diagnosis, care, treatment and disease surveillance. A paper by Mboera et al (2015) found that a well-established National Health Laboratory System was in place in Tanzania, however, the coordination of HIV laboratory services was found to be weak. The authors reported that whilst in most laboratories, guidelines for HIV diagnosis were available, health care providers were not aware of their availability.…”
Section: Laboratory Facilitiesmentioning
confidence: 99%
See 1 more Smart Citation